How to Increase Boys’ Engagement in Reading Mandatory Poems in the Gymnasium: Homer’s “The Odyssey” as Transmedia Storytelling with the Cyclopeia Narrative as a Computer Game - Pasalic, Ademir; Andersen, Nikolaj Hollænder; Carlsen, Christopher Schinkel; Karlsson, Emil Åberg; Berthold, Markus; Bjørner, Thomas (Smart Objects and Technologies for Social Good, 2018)
This paper outlines how a computer game can be used within transmedia storytelling to engage boys in the Danish gymnasium to read the epic poem “The Odyssey” by Homer. The study is based on a formative evaluation with questionnaires, observations, data logging, and interviews. Interviews with classical civilization teachers were further conducted, both in the initial design stage and after participant tests. Through all stages of the transmedia storytelling, it was revealed that curiosity was the main reason behind the engagement. The aesthetics worked out well in the game, and the story was presented in a format that the boys could comprehend and had the potential to increase their engagement in reading the poem. Different elements were implemented in the program code to maintain match in game flow for the individual player. However, this study can also emphasize how well-designed game mechanics are of ultimate importance, as well as involving teachers throughout all stages in the iterative process, as they are key figures for real implementation and acceptance.